Difference in Earnings Conservatism: The Case of Cross-Listed Firms. - Zhang, Xiaonan (2007)
In this dissertation I investigate the difference in earnings conservatism level between cross-listed companies and only domestic listed companies. Specifically, I compare conservatism levels of UK companies with a listing on the US exchange to UK companies without a US listing (only listed on London Stock Exchange) during a period from 2001 to 2005. The UK cross-listed companies are expected to be more conservative than the only domestic listed companies, mainly because the cross-listed companies on the US exchanges face a stricter enforcement regime and expect a higher litigation cost. Further, evidence shows that UK cross-listed companies tend to set the conservatism level of their reported earnings under UK (IFRSs ) GAAP similar with those under US GAAP. This consideration could also change the conservatism level of their reported earnings. According to Basu (1997), conservatism could be defined as the differential speed with which good and bad news is incorporated into reported earnings. I adopt the regression model which tests this asymmetric recognition and use a matched firm-pair method to form my sample. My result indicates that reported earnings of UK cross-listed companies are more conservative than reported earnings of domestic listed companies.